IMPACT OF SEEDLING INFECTION OF SEPTORIA TRITICI BLOTCH ON BREAD WHEAT - M. Aydoğdu (Journal of Animal and Plant Sciences, 2020)
Septoria tritici blotch (STB), caused by the fungus Zymoseptoria tritici (Roberge ex Desm.) Quaedvl. & Crous, poses a serious threat to bread wheat (Triticum aestivum L.) production around the world. Although there are various studies related to STB, impact of seedling infection on growth of bread wheat have not been well documented yet. The aims of the study were to examine host-pathogen interactions at the seedling stage and then monitor impact of seedling infection on plant growth. A total of 20 bread wheat cultivars were used as host plants and tested in the greenhouse. Seedlings of the cultivars at the two and three-leaf stages were inoculated with Z. tritici. Responses of the cultivars were determined using 0 to 5 scale. Fully-grown plants were evaluated for impact of STB on some agronomic traits (grain weight and plant height) of wheat. The cultivars showed different responses to Z. tritici. However, cvs. Adana-99, Ziyabey-98, Karatopak, Yakamoz and Ceyhan-99 were moderately resistant while cvs. Yüreğir-89 and Pamukova-97 were highly susceptible. STB infection at the seedling stage caused significant (p≤0.01) reduction in plant height ranging from 3.5 to 10.8% and grain losses 11.2 to 34.2% among the cultivars. The study suggests that when Z. tritici infects bread wheat at the seedling stage, it can significantly affect plant growth and grain yield of the crop.
Keywords: Grain loss; interaction; plant height; Triticum aestivum; Zymoseptoria tritici